ENT600: Hillside tram / Mohd Farhan Abdullah, Ahmad Haziq Zulkifli and Mohamad Shahidan Abdul Rahman - Abdullah, Mohd Farhan; Zulkifli, Ahmad Haziq; Abdul Rahman, Mohamad Shahidan (2017)
The New Product Development (NPD) consists of the activities carried out by firms or entrepreneurs when developing and launching new products. For our group's new product development, we are developing the hillside tram, an inclined elevator can go up tilted grades. 1. Problem Statement • Difficulty to transport item or people up an incline hill • People with disability have issue to use the staircase with their wheelchair • The time to climb the hill or the tilted surface is quite long and tiring when using the stairs 2. Methodology • The survey method is being used to develop the hillside tram. • We ask people who their house and facilities that located on top of the hill and near to the river bank at Sungai Pahang. • Pusat Perhilitan UiTM is one of the respondent who need this kind of technology to be install at their facilities, Kuala Keniam, Pahang. 3. Limitation • Existing product (escalator conveyer belt) cannot be install outdoor due to durability of the product • Escalator conveyer belt cannot withstand the weather change in Malaysia. • The existing product have high maintenance. At least 2 times per month. • The escalator give disadvantage for handicap. For example, people in wheelchair.